Pengaruh Supervisi Akademik Pengawas Sekolah Terhadap Kinerja Guru Mata Pelajaran IPA di SMPN Tungkal Jaya - Mujahidin Mujahidin (Universitas Islam Negeri Mataram, 2017)
Education is the essence of the nation’s progress. But in reality, it is rhetoric whereas it has been more than 65 years of independence. The low professionalism of teachers in Indonesia can be seen from the eligibility of teaching teachers. One of effort to improve the professionalism of teachers, conducted through the supervision of school academic supervisors in supervision of teacher’s performance. Thus the role of academic supervision conducted by the school supervisor is very influential in order to improve the performance of teachers in teaching. This research was conducted in Junior High School (SMPN) in Tungkal Jaya districts. This was a classroom action research which the approach used in this research was a quantitative descriptive approach. The implementation of academic supervision of school supervisors influenced the performance of teachers’ science subject at SMPN 2 Tungkal Jaya, SMPN 3 Tungkal Jaya, SMPN 4 Tungkal Jaya, SMPN 5 Tungkal Jaya, and SMPN 7 Tungkal Jaya. This study showed that the performance of the teachers’ science subject increased from the category of less good value (≤ 50) to very good (≥ 86).